Judicial convergence and fragmentation in the case-law of regional human rights bodies and the UN Human Rights Committee - Abrusci, Elena (2019)
The proliferation of regional and international human rights adjudicatory bodies increases the likelihood of conflicting interpretations of fundamental rights and freedoms, which may trigger judicial fragmentation. International Human Rights Law (IHRL) certainly offers a fertile ground for fragmentation to arise for the high sensitivity of the issues related to many human rights and the determinant role of social, cultural, religious and historical concerns. While judicial fragmentation in International Law has been at the centre of the scholarly debate in the last decade, the same phenomenon within IHRL has been less explored. The present thesis aims at providing a better understanding of the current phenomena of fragmentation and convergence in IHRL and identifying their triggering factors. In particular, it aims at answering two key research questions. First, is judicial fragmentation actually affecting IHRL or does convergence prevail? And, second, what are the factors that can be identified as contributing to this situation? Looking at the case-law of the three main regional human rights systems (African, European and Inter-American) and the UN Human Rights Committee, this thesis assesses the extent of judicial fragmentation in IHRL, concluding that the phenomenon is limited and the worries about it mostly exaggerated. Moreover, adopting a wide range of methodological approaches, this thesis identifies and explores several factors that can explain this substantial convergence and the few cases of fragmentation. On the one hand, elements strictly related to the adjudication, such as the understanding and application of the principles of necessity and proportionality, the adoption of subsidiarity and deference doctrines or the resort to judicial dialogue confirm their relevance in shaping the case-law and avoiding or triggering fragmentation. On the other hand, other factors such as the composition of the bodies and the personal profile of who decide the case, the role of registries and secretariats as well as NGOs also proved to have an influence on the judicial behaviour of these human rights bodies, ultimately affecting convergence and fragmentation.